An Old Mechanism, Imitation, Geared for Socio-Material Knowing in a “Day in the Life” of First Graders - Pinto, Giuliana; Cameron, Catherine Ann; Toselli, Monica (Frontiers in Psychology, 2020)
This paper adopts sociomateriality as a theoretical lens to further our understanding of how imitation acts to support the use of objects, and in doing so, constitues a sociomaterial practice. Within a sociomaterial perspective we aimed to perform the analysis of imitation as a powerful way to learn how to use objects embedded into the practices within which the objects are constituted. The contribution of this approach is illustrated using the findings of the application of the quasi-ecological DITL methodology to the everyday lives of two 6-year-old children. Within a case-study frame, we traced the children’s imitation behaviors focused on the use of objects during an entire day of their life, the various people and practices with which they were associated, the multiple sociomaterial configurations that the objects assume, and the social and material consequences of their use. Imitation appears to be is a complex activity, involving multiple stakeholders who interact in order to facilitate the understanding of various artifacts across diverse knowledge domains, and enhance their interpretive flexibility across communities of practice.